PENGARUH KOMUNIKASI INTERNAL, KEPEMIMPINAN, DAN PELATIHAN TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Produksi PT. Temprina Media Grafika Jawa Pos Group Semarang) - Agata, Amelia; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2015)
Printing company not only promote an good and right result, but also requires the management of human resources is appropriate. This research is intended to explain how internal communication, leadership and training development to employees performance production team on PT Temprina Media Grafika Jawa Pos Group Semarang. The data in this study were collected through a questionnaire distributed to 40 employees with a sampling technique is census at the PT Temprina Media Grafika Jawa Pos Group Semarang. The technique of testing data used in this study include theinstrument test (reliability test, validity test), the classical assumption test (normality test, heteroscedasticity, linearity test), multiple linear regression analysis, T-Tests, F Test and Coefficient of Determination Test ( R2) with SPSS 20.0. Result indicates that internal communication, and training variable are possitve and significant effect on employee performance,but leadership variable is possitive and not significant effect on employee performance. The correlation of internal communication, leadership, and training can explain employee performance variation as much as 28.6%.